Supplier Selection and Order Allocation with Lean Manufacturing Criteria: An Integrated MCDM and Bi-objective Modelling Approach. Issue 4 (1st October 2020) - Rezaei, Aida; Rahiminezhad Galankashi, Masoud; Mansoorzadeh, Shiva; Mokhatab Rafiei, Farimah
Abstract: The main aim of this research is to propose an integrated Multi-Criteria Decision Making (MCDM) and bi-objective mathematical model for supplier selection and order allocation of lean manufacturers. Despite the vast quantity of research on Lean Manufacturing (LM) and its related tools, lean supplier selection and order allocation is less studied in the previous literature. To fill this gap, this study is conducted in four phases as follows. First, an initial list of leanness criteria is extracted from previous studies. Next, using an Analytic Hierarchy Process (AHP), these criteria are examined to be applied in a supplier selection process. Following, a Fuzzy Analytic Hierarchy Process (FAHP) is applied to select the suppliers according to lean supplier selection criteria. Last, a bi-objective mathematical model is developed to determine the optimum order allocation. The developed model is verified, validated, and a sensitivity analysis is conducted to suggest managerial implications according to different values of parameters.